Germination and seedling growth of Sesbania species as influenced by seed size - Chanda, SC; Mridul, AM; Sagar, A; Sarwar, AKMG (Progressive Agriculture, 2018)
An experiment was carried out at Plant Systematics Laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh to find out the effect of seed size on germination and seedling growth of three Sesbania species. Seed size was graded as small (3.1–3.5 mm), medium (3.6–4.0 mm) and large (4.1–4.5 mm); and three Sesbania species viz. S. bispinosa, S. cannabina and S. sesban, were used as experimental materials. The treatments were arranged in factorial experiment laid in completely randomized design having four replications. Though the effect of seed size on germination and seedling growth parameters followed similar trend, significant differences were observed among these three Sesbania species. Medium-sized seed produced the highest percentage of emergence and germination, and large-sized seed produced the highest seedling length, vigour index, and total biomass; although the numerical values did not differ statistically. The small-sized seeds were poor performer in all aspect of germination and seedling growth descriptors. The correlation matrix analyses showed that seed size, both length and/or width, highly correlated with root and seedling length, base diameter, vigour index and biomass yield of Sesbania spp. The medium to large-sized seed sown at relatively higher seed rate could be helpful for higher biomass yield of Sesbania spp. especially at the early growth stages. Progressive Agriculture 28 (4): 316-322, 2017